THE IMPACT AND IMPORTANCE OF SMALL INDUSTRIAL ZONES ON THE COUNTRY’S INVESTMENT CLIMATE - Sotimov Yunusbek Turgunboy ugli (Ecomind Press, 2025)
The article analyzes the impact and economic significance of small industrial zones on the country's investment climate. It reveals the role of these zones in increasing production capacity, supporting the activities of business entities, and attracting foreign and local investments. It also highlights on a scientific basis that regional economic activity is increasing as a result of the favorable infrastructure, tax and customs privileges created through small industrial zones. The article examines the contribution of small industrial zones to socio-economic development based on an analytical approach.
Keywords: Small industrial zones, investment climate, entrepreneurship support, local production, economic development, infrastructure benefits.